Correlation and tracking using multiple radar sensors - De Villiers, Hendrik Barney (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Mathematical Sciences. Applied Mathematics))--University of Stellenbosch, 2005.